A high-repetition rate pulsed electron accelerator; IEEE Transactions on Dielectrics and Electrical Insulation; Vol. 20, iss. 4 - Egorov I. S. Ivan Sergeevich; Esipov V. S.; Remnev G. E. Gennady Efimovich; Kaikanov M. I. Marat Islambekovich; Lukonin E. I. Evgeny Ivanovich; Poloskov A. V. Artem Viktorovich (2013, 2013)
Title screen